Yep – We Can Do That: Technological response to the curriculum ‘needs’ arising… - Compton, Vicki (Design and Technology Education: An International Journal, 2009)
New Zealand has recently released a new national curriculum presented as the New Zealand Curriculum(NZC) (Ministry of Education, 2007). This document has significant implications for the future redevelopment of both the compulsory school curriculum and the noncompulsory senior secondary school curriculum. After a general introduction, this paper is divided into three main sections. In the first section, I explain the ‘givens’ presented in the NZC, these being the overarching Principles, Values and Attitudes, and the Key Competencies. I also outline the concept of ‘Learning Areas’ – as opposed to subjects. In the second section, I provide a brief overview of technology in New Zealand and present the key constructs of the revised technology learning area in the NZC. In the third section, I discuss and illustrate ways in which technology education can work to address the ‘givens’ in innovative ways that support the development of student technological literacy and general citizenship. I conclude the paper with an acknowledgement of potential issues, and express my opinion that while technology is well placed to respond to ‘needs’ arising, we should also be thinking about how much of this responsibility we should take on.